Frequency of uropathogens showing resistance to Nitrofurantoin - Tariq Mahmud Tariq (Journal of the Pakistan Medical Association, 2023)
Urinary tract infection (UTI) caused by bacteria is the commonest infection accountable for the unforeseen healthcare cost throughout the globe. Nitrofurantoin is being studied as a solution to the perpetually increasing threat of antimicrobial resistance. The objectives of this study were to determine the frequency of urinary isolates causing UTI and their susceptibility pattern against Nitrofurantoin. Data of all isolates reported as uropathogens from April 1, to December 31, 2021, was collected through Electronic Medical Record system of Shalamar Hospital, Lahore. Results of Nitrofurantoin susceptibility were recorded to find the resistance pattern of bacterial isolates. Out of a total of 3,221 samples, 672 (20.9%) were positive with significant bacteriuria. Of the positive samples, 418 (62.2%) were collected from females and 254 (37.8%) from males, with female to male ratio of 1.65:1. The number of female patients was higher in adult age. ---Continue